(untitled) (Research, Society and Development, 2024)
Objective: Here we investigate the impact of involuntary and temporary interruption of hydroxyurea (HU) treatment in patients with Sickle Cell Disease (SCD). Methods: Clinical and hematological parameters were explored in 30 patients with SCD under treatment with HU. The study was performed in two different periods: 1 - During nine months of involuntary discontinuation (April/2015 to January/2016) and 2 – During nine months after resumption of the treatment (March/2016 to December/2016). Results: The resumption of HU treatment improved the hematological parameters, by increasing levels of hemoglobin (+0.65±0.71), hematocrit (+1.16±2.26), mean corpuscular volume (+8.33±5.89), mean corpuscular hemoglobin (+3.15±2.65). There was a reduction in red blood cell distribution width (-0.66±1.69), reticulocytes (-2.53±1.96), leukocytes (-1122±2764) and platelets numbers (-79.933±162.756). These was followed by a reduction in hospital admissions (-0.30±0.79) and in the number of pain episodes (-0.97±1.19), whereas the denial in episodes of pain crisis increased (+1.43±1.43). After resumption, in period 2, hemoglobin levels were inversely correlated with blood transfusion numbers (p=0.034) and acute thoracic syndrome (p=0.017). The hematocrit was inversely correlated with the number of consultations (p=0.030) and the number of times patients denied crisis (p=0.002). Conclusions: Our study shows that the treatment with HU improves clinical and haematological parameters in patients and highlights the negative effects of the discontinuation of the treatment in the quality of life in patients with SCD.